From Cape Town to Kabul Rethinking Strategies for Pursuing Women's Human Rights - Andrews, Penelope (2012)
Using her experience of living under apartheid and witnessing its downfall and the subsequent creation of new governments in South Africa, the author examines and compares gender inequality in societies undergoing political and economic transformation. By applying this process of legal transformation as a paradigm, the author applies this model to Afghanistan. These two societies serve as counterpoints through which the book engages, in a nuanced and novel way, with the many broader issues that flow from the attempts in newly democratic societies to give effect to the promise of gender equality. Developing the idea of 'conditional interdependence', the book suggests a new approach based on the communitarian values which underpin newly democratic societies and would allow women's rights to gain momentum and reap greater benefits. Broad in its thematic approach, the book generates challenging and complex questions about the achievement of gender equality. It will be of interest to academics interested in gender and human rights, international and comparative law.